Lean model applying JIT, kanban, and standardized work to increase the productivity and management in a textile SME - Canales Jeri, Luis Eduardo (2024)
The competitiveness in the textile industry has been significantly increasing because of better conditions in terms of quality and volume offered by foreign industries. In addition to this situation, the low productivity and late deliveries become principal factors that cause the lack of development in the Peruvian SMEs. As a solution to this issue, it's essential to act on the production and warehouse management by using lean manufacturing tools such as JIT, Kanban, and Standardized Work. This case of study proposes an integrated model which sets the environment to reduce some critical indicators such as defective products (20%) or out-of-time delivery rate (60%). Those indicators are currently above the industry, and we pretend to make the company competitive by reducing 13% and 30% respectively after the validation. Using these results, we can confirm the effectiveness of Kanban, JIT, and Standardized work as tools to improve the efficiency and Agility in production and warehouse management.